Internalization of the Character of Piety at the As-Shidqu Kuningan Islamic Boarding School - Rokhman, Abdul; Perawironegoro, Djamaluddin; Hopid, Abdul (Early Publishing, 2025)
This research is motivated by the gap between religious understanding and religious practices of some students at the As-Shidqu Kuningan Islamic Boarding School, such as inconsistencies in participating in congregational prayers, qiyām al-layl, recitation, and violations of pesantren discipline. This study aims to analyze the process of internalizing the character of piety through learning Tafsir Jalalain on QS Al-Baqarah verses 1–5. This research uses a qualitative approach with a case study type. The research subjects were selected purposively, consisting of kiai, two Tafsir Jalalain teaching ustaz, and four students. Data were collected through participatory observation, in-depth interviews, and documentation studies, then analyzed using the Miles and Huberman model through data reduction, data presentation, and conclusion drawn. The results of the study show that the internalization of the character of piety takes place through the integration of religious learning, worship habits, kiai examples, ta'zhīm culture, discipline, and ta'zīr system. This process is in line with the Social Construction Theory of Peter L. Berger and Thomas Luckmann, namely the externalization of values by kiai and ustaz, the objectification of values in pesantren culture, and the internalization of values into the awareness and behavior of students. This study concludes that the formation of pious character requires a consistent, collective, and sustainable religious environment.